Implementation of Merdeka Belajar Curriculum in Elementary Schools: How is Teachers' Perception? - Dasep Supriatna; Sitti Nadirah; Aniati; Ali Rahman; Mia Aina; Arif Saefudin (International Journal of Education, Vocational and Social Science, 2023)
The purpose of this study was to describe teachers' perceptions of the implementation of an independent curriculum in elementary schools. This research is qualitative. Qualitative research explores and understands the meaning of several individuals or groups of people with social problems. The researchers construct reality and understand the meaning, so this research strongly focuses on processes, events, and authenticity. The respondents were elementary school teachers. Data were collected through interviews. The main instrument of this study was the researcher, supported by field notes. All data were collected and reviewed descriptively to obtain reliable and trustworthy findings. The results showed that: (1) teachers' perceptions are positive and good towards the implementation of the Merdeka curriculum in elementary schools, (2) teachers play an essential role in the process of curriculum development and implementation in elementary schools, and the success of curriculum implementation depends on the intensity with which teachers implement the curriculum in the classroom, (3) teachers can develop and implement curriculum and design classes to improve learning quality; (4) socialisation and special technical guidance related to the formation of the Pancasila learner profile have not been maximised; (5) not all elementary school teachers have adopted Merdeka curriculum; (6) not all teachers have information technology skills; and (7) the obstacle in implementing Merdeka curriculum is the lack of stable internet access, especially for remote schools that have geographically difficult internet access.